Utilization of Corn Husk Waste as Raw Material for Making Biobutanol - Dyah Suci Perwitasari; Graciella Yerrica Nathania; Abid Alghifari (Future Science, 2023)
Corn husk waste is a biomass raw material that can be processed into biobutanol. Making biobutanol to reduce the use of fossil fuels. This research used anaerobic microorganisms, namely Clostridium acetobutylicum, which can survive at low pH between 4,5 and 5 at a temperature of 30°C. Corn husk contains 36.218% cellulose; 25.212% hemicellulose; 15.807% lignin. The cellulose raw material content can be used for fermentation because it meets the fermentation content requirements of 36 – 50%. The research methods used include raw material preparation, delignification, dilute acid hydrolysis, and anaerobic fermentation. The research results showed that optimum condition was obtained at the 72-hour fermentation time with the addition of a 5% Clostridium acetobutylicum bacteria volume of 7.0160%. At the 72 hour fermentation time, it showed that the bacteria grew optimally and entered the stationary phase. Biobutanol levels after 72-hour decreased due to reduced nutrients in the fermentation media. The increase in the volume of bacteria affects the final results, the volume of bacteria is added, the final results biobutanol levels will decrease because the nutrients added have been used up. The results of the analysis of butanol levels were determined using Gas Chromatography, the standard for butanol formation obtained at a retention time of 3.598%. The low butanol content (7,0160%) does not require industry standards (96.5 – 99%) to be used as environmentally friendly fuel, due to obstacles in maintaining anaerobic fermentation conditions and not carrying out fermentation filtrate sterilization, which has an impact on the final result of biobutanol content.ly and requires improvement, particularly in the quest for zero defects.